Large Scale Renewable Power Generation Advances in Technologies for Generation, Transmission and Storage - Hossain, Jahangir; Mahmud, Apel (Green Energy and Technology,, 2014)
This book focuses on the issues of integrating large-scale renewable power generation into existing grids. The issues covered in this book include different types of renewable power generation along with their transmission and distribution, storage, and protection. It also contains the development of medium voltage converters for step-up-transformer-less direct grid integration of renewable generation units, grid codes and resiliency analysis for large-scale renewable power generation, active power and frequency control, and HVDC transmission. The emerging SMES technology for controlling and integrating large-scale renewable power systems is also discussed. Since the protection issues with large-scale distributed renewable power systems are different compared to the existing protection system for one way power flow, this book includes a new protection technique for renewable generators along with the inclusion of current status of smart grid. This book is a good reference for the researchers who are working the area of renewable power generation and smart grids.